2007
DOI: 10.1017/s0007114507433001
|View full text |Cite
|
Sign up to set email alerts
|

Survival and metabolic activity of selected strains ofPropionibacterium freudenreichiiin the gastrointestinal tract of human microbiota-associated rats

Abstract: In addition to their use in cheese technology, dairy propionibacteria have been identified as potential probiotics. However, to have a probiotic effect, propionibacteria have to survive and to remain metabolically active in the digestive tract. The aim of the present study was to investigate the survival and metabolic activity of Propionibacterium freudenreichii within the gastrointestinal tract of human microbiota-associated rats, and its influence on intestinal microbiota composition and metabolism. Twenty-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 66 publications
(101 reference statements)
3
72
0
1
Order By: Relevance
“…Seven days later, fecal strict anaerobes, facultative anaerobes, and enterobacteria were numerated to check for colonization. The level of each population was similar to the normal population levels of human feces, indicating successful colonization of the rat digestive tract by the complex human microbiota, as previously described (20). We did not directly inoculate the rats with E. coli O157:H7 because it is known that EHEC colonizes the gut of conventional rodents to a much lesser extent than the guts of germfree or streptomycin-treated rodents (27,28).…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Seven days later, fecal strict anaerobes, facultative anaerobes, and enterobacteria were numerated to check for colonization. The level of each population was similar to the normal population levels of human feces, indicating successful colonization of the rat digestive tract by the complex human microbiota, as previously described (20). We did not directly inoculate the rats with E. coli O157:H7 because it is known that EHEC colonizes the gut of conventional rodents to a much lesser extent than the guts of germfree or streptomycin-treated rodents (27,28).…”
Section: Resultssupporting
confidence: 53%
“…They were given free access to sterile water and a pelleted semisynthetic diet (Scientific Animal Food and Engineering, Augy, France) sterilized by ␥ irradiation at 40 kGy (IBA Mediris, Fleurus, Belgium). To reproduce the diversity of a human-type diet, the food contained lipids and proteins of animal and plant origins, sucrose, and cooked starch (20). Throughout the study, isolators were maintained in controlled conditions of light, temperature, and humidity.…”
Section: Methodsmentioning
confidence: 99%
“…Survival of propionibacteria during gastrointestinal transit has also been reported in vivo in rats [125,126]; mice [124,137] and humans [127,130,133]. Furthermore, Herve et al [34], demonstrated that propionibacteria remain metabolically active since the P. freudenreichiispecific transcarboxylase mRNA was detected in human faeces.…”
Section: Safety and Persistence In The Gutmentioning
confidence: 92%
“…At present, no cases of sickness or toxicity after the ingestion of dairy propionibacteria have been reported [122] neither for humans (for a review of human trials see [123]) nor for animals [124][125][126]. In fact, it has been reported that propionibacteria did not translocate to blood, liver or spleen and no adverse effects on body weight gain and general health status was observed after short [124,127] and long terms [125] administration of strains of Propionibacterium acidipropionici, P. freudenreichii and P. jensenii, respectively.…”
Section: Safety and Persistence In The Gutmentioning
confidence: 99%
“…Tolerance toward digestive stresses was shown in vitro to be highly strain dependent in P. freudenreichii strains (36). Compared to their corresponding WT strains, the three KO mutants showed different survival rates under acidic and bile salt stresses, although these differences did not reach significance.…”
Section: Figmentioning
confidence: 95%